JAVANESE CAMPURSARI AND HISTORICAL ENTITY : A LINGUISTIC RELATIVITYOF JOKO TINGKIR NGOMBE DAWET - Puspita, Kharisma (Sekolah Tinggi Bahasa Asing Prayoga Padang, 2025)
Javanese campursari is one of the identical kinds of music for Indonesian people even for Javanese people. This type of music has some characteristics such as containing light lyrics, sometimes using comedy or parody, and varying a kind of specific gesture or goyangan. A problem occurred when a symbol of the historical entity who was an ancestor of ulama/great religious spreader namely Prabu Jaka Tingkir or Mas Karebet or Sultan Hadiwijaya was used as contain of musical parody. The current researcher decided to embrace an anthropological study, especially the theory of linguistic relativity in exploring this social polemic by taking three components for example as language, language users, and worldview. Some YouTube channel sources were taken as primary data sources while other links to popular news articles would be also secondary data. The qualitative technique and contextual approach were engaged as data analysis techniques. Hence, a technique of content analysis by stepping three components such coding selection, classifying unit, and explaining contextual analysis. According to those analyses, the newest researcher concluded that the young generation has only limited insight into historical symbols in Indonesia so a specific material of historical entity was needed to be inserted in the basic curriculum.